SLC6A8 is a Potential Biomarker for Poor Prognosis in Lung Adenocarcinoma - Fan, Yongfei; Zhou, Yong; Lou, Ming; Gao, Zhaojia; Li, Xinwei; Yuan, Kai (Frontiers in Genetics, 2022)
Background: Recent studies have demonstrated that creatine can promote tumor metastasis and has implications for immune cell function. SLC6A8 encodes a membrane protein that can transport creatine inside and outside the cell. However, there are currently no studies of SLC6A8 in lung adenocarcinoma (LUAD). Methods: In this study, the expression of SLC6A8 in LUAD was analyzed using the Oncomine database, the Cancer Genome Atlas (TCGA) database, and immunohistochemical staining analysis. Survival analysis of patients with LUAD was performed using the cBioPortal and the Kaplan-Meier Plotter websites and clinical follow-up data. An analysis of the association between SLC6A8 and the tumor immune microenvironment (TIME) of LUAD was performed through the TISIDB database and estimation of stromal and immune cells in malignant tumor tissues using expression data (ESTIMATE) algorithm. Then, based on the curated list of SLC6A8-related immunomodulators, three genes (NT5E, CD40LG, CD80) were selected to construct SLC6A8-related immune signatures to further evaluate the immune aspect of LUAD prognosis. Results: Our studies indicated that SLC6A8 was overexpressed in LUAD, and the high expression of SLC6A8 was associated with poor survival. Genetic alteration of SLC6A8 was also associated with a poorer prognosis. Furthermore, multivariate Cox analysis indicated that SLC6A8 could be used as an independent risk prognostic factor. Then, immune infiltration analysis indicated that SLC6A8 was also strongly associated with poor prognosis in the TIME of LUAD. A multivariate Cox proportional hazard model was then constructed, and was shown effective at identifying high-risk patients. Univariate and multivariate Cox analysis showed that the risk scoring of the model was an independent prognostic risk factor in LUAD. Conclusion:SLC6A8 may serve as a biomarker for poor prognosis in LUAD.